SUBSTITUSI TEPUNG AMPAS KELAPA DALAM PEMBUATAN BROWNIES KUKUS TERHADAP SIFAT ORGANOLEPTIK DAN NILAI GIZI - Septiani Septiani; Nur hiyanah (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
The utilization of coconut pulp flour in the food product making is still very limited. This research to analyze brownies that are distuited coconut pulp flour against nutritional value. This research is an experimental research with level of substitution of wheat flour with coconut pulp flour as treatment. There are 3 treatments, that is F1 (55% wheat flour and 45% coconut pulp flour), F2 (45% wheat flour and 55% coconut pulp flour) ad F3 (35% wheat flour and 65% coconut pulp flour). Formula results selected from the organoleptic test who is F1 with comparison 55:45 continued with result proximate test that obtained water rate, ash rate, fat, protein, carbohydrate and fiber in way continue that 23,88%, 1,91%, 7,39%, 5,78%, 61,04 and 1,82%. The conclusion of this research is that have differences (p <0.05) between the formula result to water rate, ash rate, protein, carbohydrate and fiber.